2019
DOI: 10.1002/zoo.21472
|View full text |Cite
|
Sign up to set email alerts
|

Digestive physiology of captive capybara (Hydrochoerus hydrochaeris)

Abstract: The capybara (Hydrochoerus hydrochaeris), the largest living rodent, probably has a “mucus‐trap” colonic separation mechanism. To test this hypothesis, we measured the mean retention time of a solute marker (MRTSolute), 2 mm (MRT2 mm), 10 mm (MRT10 mm), and 20 mm (MRT20 mm) particle markers and nutrient digestibility in adult captive capybaras (27–52 kg body mass (BM), 2–11 yr). In addition, total gut fill and the selectivity factor (MRTSolute/MRT2 mm) were calculated, and mean faecal particle size and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Lall et al [96] summarized these animals as semi-aquatic herbivorous rodents that practice cecotrophy. These animals are hindgut fermenters that possess a mucus trap separation mechanism [109]. Various parasites have been found in the capybara, but the majority of research views these animals as reservoirs for specific pathogens that have zoonotic potential or can cause disease in domestic livestock species.…”
Section: Capybara (Hydrochoerus Hydrochaeris)mentioning
confidence: 99%
“…Lall et al [96] summarized these animals as semi-aquatic herbivorous rodents that practice cecotrophy. These animals are hindgut fermenters that possess a mucus trap separation mechanism [109]. Various parasites have been found in the capybara, but the majority of research views these animals as reservoirs for specific pathogens that have zoonotic potential or can cause disease in domestic livestock species.…”
Section: Capybara (Hydrochoerus Hydrochaeris)mentioning
confidence: 99%
“…The capybara ( Hydrochoerus hydrochaeris ) is the largest living rodent, typically found in the Pantanal wetlands and Amazon basin, and it is also known as “the master of the grasses” due to its diet based on gramineous and aquatic plants. In this animal, the fermentation takes place in the cecum that corresponds to almost three-quarters of the gastrointestinal tract, reaching a digestive efficiency comparable to that of ruminants 12 . Moreover, as a strategy to maximize absorption of nutrients derived from bacterial fermentation, capybara can eat their cecotropes, a specific type of soft excreta 13 .…”
Section: Introductionmentioning
confidence: 97%
“…Capybara (Hydrochoerus hydrochaeris) is the largest living rodent throughout found in Pantanal wetlands and the Amazon basin, which is also known as "Master of the grasses" due to its diet. In this animal, the fermentation takes place in the cecum, which corresponds to almost three quarters of the digestive tract, reaching a digestive e ciency comparable to that of ruminants (12). Preliminary characterization of capybara cecum microbiome indicated that the most abundant commensal microbes were from Firmicutes and Proteobacteria phyla, with an unusual low abundance of Bacteroidetes (13), not expected for a typical mammalian hindgut fermenter.…”
Section: Introductionmentioning
confidence: 92%